2014
DOI: 10.2217/pgs.14.142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Major Transporter and Metabolizing Enzyme Gene Polymorphisms on Carbamazepine Metabolism in Chinese Patients with Epilepsy

Abstract: Our data suggest that certain polymorphisms of major transporter and metabolizing enzyme genes could in part influence interindividual variability of CBZ metabolism in Chinese patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…In 84 Chinese patients, lower trough concentration (C 0 ) values in those with the 3435TT genotype were reported [190]. A recent study in 210 Chinese patients showed that 3435CT carriers had lower C 0 /D values [191]. A lower response rate in carriers of the 2677TT genotype was reported [192], whereas 3435TT had no significant effect [193].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…In 84 Chinese patients, lower trough concentration (C 0 ) values in those with the 3435TT genotype were reported [190]. A recent study in 210 Chinese patients showed that 3435CT carriers had lower C 0 /D values [191]. A lower response rate in carriers of the 2677TT genotype was reported [192], whereas 3435TT had no significant effect [193].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Furthermore, evidence of microsomal epoxide hydrolase activity at or near the blood-brain barrier has been reported (Ghersi-Egea et al, 1994). Carbamazepine, phenobarbital, and phenytoin are three xenobiotics with well characterized metabolic pathways involving epoxide hydrolase, with recent evidence suggesting that single nucleotide polymorphisms in the microsomal epoxide hydrolase gene EPHX1 influence carbamazepine exposure in vivo (El-Sherbeni and El-Kadi, 2014;Zhu et al, 2014;Daci et al, 2015).…”
Section: Epoxide Hydrolasesmentioning
confidence: 99%
“…Carbamazepine (CBZ), a first-line antiepileptic drug, has been widely prescribed for the treatment of partial and generalized tonic-clonic seizures. It has been reported that CYP3A5*3 is associated with CBZ pharmacokinetics in Japanese [ 20 ], Korean [ 21 ], and Chinese [ 22 ] epileptic patients, and that CYP3A5 expressers are more likely to require higher CBZ maintenance doses than nonexpressers (GA + AA vs. GG). The CYP3A5 genotype may also have dose-dependent effects on ABT-773 plasma levels.…”
Section: Discussionmentioning
confidence: 99%